Psidium guajava L. hydroethanolic extract as endodontic irrigant: phytochemical analysis, antioxidant activity, antimicrobial action and biocompatibility - de Carvalho, Lara Steffany [UNESP]; Meccatti-Domiciano, Vanessa Marques [UNESP]; da Silva, Livia Ramos Dorta [UNESP]; Marcucci, Maria Cristina [UNESP]; Carvalho, Cláudio Antonio Talge [UNESP]; Abu Hasna, Amjad [UNESP]; de Oliveira, Luciane Dias [UNESP] (PeerJ, 2025)
Background: The search for novel antimicrobial agents in Endodontics is constant to overcoming persistent infections. Psidium guajava L. is a medicinal plant little explored in Endodontics. The aim of this study was to produce hydroethanolic extract of P. guajava L. and to evaluate its phytochemical composition, antimicrobial and antibiofilm action against standard and clinical strains of Enterococcus faecalis and Candida albicans, and cytotoxicity and genotoxicity on human keratinocyte cultures (HaCaT cells). The findings provide new insights into the potential of P. guajava as an alternative endodontic antimicrobial agent, contributing to the development of more effective and biocompatible therapeutic strategies. Methods: P. guajava hydroethanolic extract was produced using young leaves of guajava and extracted using absolute ethanol and ultrapure water in a ratio (30 g:100 mL). The solid soluble, total flavonoid and total phenols content were determined. The chemical composition was determined via high-performance liquid chromatography (HPLC) analysis, then the free radical suppressive activity was assessed by determining the IC50 value, indicating the concentration required to eliminate 50% of free radicals. Later, the minimum inhibitory concentration (MIC) and minimum microbicidal concentration (MMC) of the extract was evaluated against the strains using clinical and laboratory standards institute (CLSI) guidelines (M27-S4 and M7-A9). Then, the antibiofilm activity was evaluated via MTT (3-[4,5-dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium bromide) assay. Finally, the cytotoxicity of the extract was evaluated via Alamar Blue assay, and the genotoxicity via micronucleus assay on human keratinocyte cultures (HaCaT cells). Data were analyzed using ANOVA and Tukey's test or Kruskal-Wallis and Dunn's test. Results: The soluble solids content in the extract was 3.35%. Using the quercetin standard curve, the total flavonoid concentration was 0.130 ± 0.110 mg/mL. In addition, using standard curve for phenolic acids, the total phenolic concentration was 1.770 ± 1.540 mg/mL. HPLC analysis revealed peaks of rutin, quercetin and kaempferol as major flavonoids in the P. guajava L. extract. The extract demonstrated notable antioxidant activity, with an IC50 value of 10.39 µg/mL. The MMC values ranged 1.04-8.37 mg/mL. The extract at 8.37 mg/mL was effective in reducing the biofilms of standard and clinical strains of E. faecalis and C. albicans after 10 min. Cytotoxicity analysis revealed that all tested concentrations exhibited relatively low toxicity toward HaCaT cells. Genotoxicity assessment via the micronucleus assay indicated minimal DNA damage at all tested concentrations. Overall, P. guajava L. hydroethanolic extract at 8.37 mg/mL is the most effective concentration in reducing the biofilm of the standard and clinical strains of E. faecalis and C. albicans, while maintaining biocompatibility with HaCaT cultures.